Simulated jury and brain storm: Understanding the implementation of Belo Monte Hydroelectric dam - Marcos Marques Formigosa; Marli Terezinha Quartieri; José Cláudio Del Pino; Miriam Ines Marchi (Universidade Federal do Norte do Tocantins, 2017)
The physics teaching still finds many obstacles in basic education, mainly because of the strong resistance that we find within its methodologies, still centered in the didactic book and the memorization of formulas and laws. This manuscript aims to present the results of the strategies of Simulated Jury and Brain Storm developed in a Countryside Education Degree (emphasis in Natural Sciences), specifically at Fundamentals of Physics III in two classes of the 4th Period, in the countryside Of Paraense Amazon. In one class we used the strategy Cerebral Storm and another strategy was the Simulated Jury, the Electricity content. The analyzes were made based on the reports of the students in the class and notes made by the teacher/researcher. These developed strategies allowed the rupture of the stereotypes presented among the students about the methodologies used by their teachers in teaching Physics contents, which was based on traditional expository classes, and with the strategies used they realized that they can approach the contents of and, above all, led them to a critical reality understanding in which they are inserted.